Neuropharmacological effects of Aconiti Lateralis Radix Praeparata. (23rd January 2020) - Zhao, Lihong; Sun, Zhihui; Yang, Limin; Cui, Ranji; Yang, Wei; Li, Bingjin
Abstract: Aconiti Lateralis Radix Praeparata (Fuzi in Chinese), which are the lateral roots of Aconitum Carmichaelii Debx, is widely used in China to treat many neurological diseases. Fuzi, in its various forms, has many neuropharmacological effects. It can act as an analgesic and help with depression, epilepsy, and dementia. However, the neuropharmacological effects of Aconiti Lateralis Radix Praeparata are seldom comprehensively reviewed. In this review, the neuropharmacological activities of some components contained in Aconiti Lateralis Radix Praeparata are considered. These include aconitine, mesaconitine, hypaconitine, total alkaloid, polysaccharide‐1, benzoylmesaconine, fuziline, songorine, and napelline. We also specifically discuss the antidepressant effects of total alkaloids and polysaccharide‐1. This review may provide a theoretical basis for further utilization of Aconiti Lateralis Radix Praeparata for diseases that affect the central nervous system.